Antioxidant properties and antiproliferative effect of brewers' rice extract (temukut) on selected cancer cell lines - Tan, Bee Ling; Mohd Esa, Norhaizan; H. J., Suhaniza; Lai, C. C.; Saad, Norazalina; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Temukut, or brewers’ rice, is a mixture of broken rice, rice bran, and rice germ. Extensive studies have been conducted on rice bran, which possesses various health benefits. Temukut, however has been less well studied. The present study aimed to investigate the antioxidant and growth inhibition properties of temukut extract using colon cancer (HT-29), ovary cancer (Caov-3), and liver cancer (HepG2) cell lines. The antioxidant activity was determined by the β-carotene bleaching assay, analysis of the DPPH radical scavenging capacity, and a FRAP assay. The total phenolic compounds, oryzanol, vitamin E, and phytic acid levels in temukut were also investigated. The antiproliferative activity was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. There was a significant difference in the cytotoxicity of two types of temukut extract (water and methanol) for HT-29 and Caov-3 cells(p < 0.05) but not for HepG2 cells. The HepG2 cell line is the least sensitive to temukut, (IC 50 = 55.30 μg/mL), whereas the highest sensitivity was observed in Caov-3 cells (IC 50=36.67 μg/ mL). No cytotoxic effect of temukut was observed on normal cells (BalBlc3T3). Although the content of the phytochemicals studied (total phenolic compounds, vitamin E, oryzanol, and phytic acid) in temukut was lower than that in rice bran, as has been previously reported, the present study demonstrated temukut’s potential to inhibit the proliferation of HT-29, Caov-3, and HepG2 cells.